Determinants of International Public Sector Accounting Standards (IPSAS) Adoption: An Institutional, Political, and Cultural Perspective from Developing Economies - Richard Doe Dartey; Jignesh Valand (International Journal of Economics, Management and Accounting (IJEMA), 2025)
This study examines the institutional, political, and cultural determinants influencing the adoption of International Public Sector Accounting Standards (IPSAS), with a particular focus on developing economies such as Ghana. The research employs a qualitative descriptive approach based on an extensive review of academic literature, policy documents, and reports from international organizations. Drawing on institutional theory, the study identifies ten critical factors shaping IPSAS adoption: awareness level, implementation cost, technical capacity, education and experience, expertise availability, top management support, external pressure, technological readiness, transition management, and strategic planning. Evidence from prior studies suggests that IPSAS adoption is primarily driven by institutional pressures, including coercive influences from international organizations and mimetic tendencies among countries seeking legitimacy (Amiri & Hamza, 2020); (Chatti et al., 2024). Additionally, empirical findings indicate that factors such as training, cost, and technological infrastructure significantly influence successful implementation (Ademola et al., 2019). The study contributes to the literature by integrating institutional and contextual perspectives to explain IPSAS adoption behavior. It provides policy-relevant insights for governments aiming to enhance transparency, accountability, and comparability in public sector financial reporting.